Headache as an initial symptom in ischemic stroke: a case report - Silva, Jonathan Lima de Oliveira; Pieri, Gabriel; Trench, Flávia Julyana Pina (Headache Medicine, 2024)
Introduction More than 60% of strokes worldwide are ischemic, classified into thrombotic, embolic, and systemic hypoperfusion etiologies. Headache or migraine can manifest as clinical symptoms, more commonly observed in hemorrhagic strokes, which typically present with decreased consciousness levels and early neuroimaging changes. Objectives To report a case of an elderly individual who presented suddenly with headache and visual changes as the sole neurological symptoms. Case Report A 63-year-old Caucasian male truck driver presented with severe holocranial headache, left amaurosis, and dizziness, seeking medical attention two days after symptom onset and receiving only symptomatic treatment. The sole neurological alteration observed was a poorly reactive left pupil, alongside a BP of 260/117 mmHg. Cranial CT revealed a small cortico-subcortical hypodensity in the right occipital lobe extending into the parietal lobe. Discharged the same day, he deteriorated the following day with left hemibody paresthesia and dysarthria, necessitating hospitalization. Over two days, he experienced hypertensive episodes with agitation and confusion. His medical history included diabetes and arterial hypertension, managed with Cinnarizine, Losartan, Hydrochlorothiazide, and Carvedilol. Transferred to a municipal hospital five days later in poor condition and sedated, he exhibited isochoric, reactive pupils, a Glasgow Coma Scale score of 6, noisy breathing, tachypnea, and a distended abdomen. In the ICU, Doppler ultrasound revealed bilateral intimal-medial thickening of the common carotid arteries, with less than 50% stenosis in the internal carotid arteries. Repeat CT ruled out intracerebral hemorrhage. Neurology diagnosed acute ischemic stroke in the occipital region based on brainstem hypodensities and extensive bilateral cortical and subcortical areas. Despite intensive care, the patient deteriorated progressively with multiple fever peaks and inadequate treatment response, showing no improvement in consciousness. After two weeks in the ICU, he experienced cardiopulmonary arrest and did not respond to resuscitation efforts, succumbing 21 days after headache onset. Conclusion Headaches are often underestimated and managed symptomatically, even when accompanied by warning signs such as visual changes and dizziness, as illustrated in this case. Therefore, a reevaluated approach to seemingly straightforward cases is crucial, considering that isolated headaches or migraines may indicate a poor prognosis, particularly in elderly patients with cardiovascular comorbidities.